1996
DOI: 10.21273/horttech.6.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Sea Buckthorn (Hippophae rhamnoides L.): A Multipurpose Plant

Abstract: Sea buckthorn (Hippophae rhamnoides L.) is a multipurpose, hardy, deciduous shrub, an ideal plant for soil erosion control, land reclamation, wildlife habitat enhancement, and farmstead protection. It has high nutritional and medicinal values for humans. The majority of sea buckthorn research has been conducted in Asia and Europe. It is a promising new crop for North America, and recently it has attracted considerable attention by researchers, producers, and industry. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 19 publications
0
122
0
1
Order By: Relevance
“…Although propagation using seeds is an easy and inexpensive method, it is impossible to distinguish the male and female plants until they start to flower. Also, some desirable traits of the parents may not be expressed in seedpropagated plants (Li and Schroeder 2003). Clonal multiplication of selected elite germplasm is meaningful for maintenance of superior traits which otherwise will be lost due to open pollination and out crossing.…”
Section: Conventional Propagation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although propagation using seeds is an easy and inexpensive method, it is impossible to distinguish the male and female plants until they start to flower. Also, some desirable traits of the parents may not be expressed in seedpropagated plants (Li and Schroeder 2003). Clonal multiplication of selected elite germplasm is meaningful for maintenance of superior traits which otherwise will be lost due to open pollination and out crossing.…”
Section: Conventional Propagation Methodsmentioning
confidence: 99%
“…Section Hippophae has H. salicifolia, H. rhamnoides (with 8 subspecies) and H. goniocarpa (with 2 subspecies), and section Gyantsenses includes H. gyantsensis, H. neurocarpa (with 2 subspecies) and H. tibetana. However, Li (2003) has reported that the genus Hippophae is composed of 6 species and 12 subspecies. On the contrary, according to Bartish et al (2002); Swenson and Bartish (2002) and Sun et al (2002Sun et al ( , 2003 this genus has 7 species and 8 subspecies.…”
Section: Problems To Be Addressed In Sea Buckthornmentioning
confidence: 99%
See 2 more Smart Citations
“…The region also produces good quality walnut and almond, but their population stands are thin and scattered throughout the region (Rana et al 2003;Dhillon et al 2005). Hippophae rhamnoides (sea buckthorn, charma) has good nutritional properties, antioxidant activity, bioactive oil used for skin care and other uses in the cosmetic and pharmacy industries (Li and Schroeder 1996;Yang et al 2001;Zeb 2004;Dwivedi and Ahmed 2006;Chauhan et al 2008;Jain et al 2008). Several herbal products and drinks like herbal multivitamin beverage, herbal appetizer, sea buckthorn nectar, and medicated herbal health beverages are traded in the market.…”
Section: Weps As Source Of Incomementioning
confidence: 99%